Postoperative rectal irrigation after laparoscopic Swenson pull-through: is early instrumentation safe? - Nikhil R Shah; Kathryn M Maselli; Gabriella Kim; Paris D Rollins; Peter F Ehrlich; Marcus D Jarboe; Matthew W Ralls (World Journal of Pediatric Surgery)
Background In approaching surgical correction of Hirschsprung disease (HSCR), laparoscopic Swenson endorectal pull-through (Lap-S-ERPT) requires less transanal dissection and sphincter stretch. This may lead to more immediate postoperative obstructive symptoms. While antibiotics and rectal irrigations are mainstays of treatment, there is concern about rectal instrumentation in the setting of recent low anal anastomosis. The purpose of this study was to assess the incidence and safety of early rectal irrigations following Lap-S-ERPT.Methods This is a single-center, retrospective review of all pediatric patients who underwent Lap-S-ERPT for HSCR from January 2018 to October 2023. Irrigations were performed if patients had obstructive symptoms including emesis, obstipation, and dilated colonic loops on radiographs. The primary outcome was need for postoperative rectal irrigation. Secondary outcomes included time from surgery to irrigation, duration of irrigation, and incidence of anastomotic leak.Results A total of 37 patients (62% male) underwent a Lap-S-ERPT at a median age of 3 months (interquartile range (IQR): 0.5, 5.0). Rectosigmoid disease was the most common diagnosis (n=29, 78.4%). There were 11 patients underwent rectal irrigations with a median time to initiation of irrigation of 46 hours (IQR: 32.0, 114.0) postoperatively and a median duration of irrigations of 3 days (IQR: 2.0, 4.5). There was no difference in anastomotic leak rate between patients who received irrigations and those who did not (9.1% v.s. 7.7%, p=0.887).Conclusion Following Lap-S-ERPT, nearly 30% of patients underwent rectal irrigation for postoperative obstructive symptoms. Despite concerns about instrumentation with a recent low anastomosis, there was no increase in leak rate in patients who received rectal irrigations.